Determination of craze initiation stress in very small polymer specimens - De Focatiis, D; Buckley, C (2008)
A miniature test method is presented for measuring craze initiation stress in tension on very small specimens of glassy polymers (less than 10 mg). The method consists of three-point bending creep experiments followed by low-power optical microscopy to determine the length of the crazed region, and hence the stress at which crazes initiate within a given time. The test method is especially suitable when extremely limited quantities of material are available. It is illustrated by application to two monodisperse and one polydisperse polystyrenes (PS). In polydisperse PS crazed in diethylene glycol, craze initiation stress and time dependence are close to those of the monodisperse PS with the same Mw, but in polydisperse PS crazed in air, crazes initiate at larger stresses, and the time-dependence is close to that of the monodisperse PS with the same Mn. The findings are discussed in terms of changes in craze initiation mechanisms from disentanglement crazing to chain scission crazing with increasing molecular weight and decreasing time. © 2007 Elsevier Ltd. All rights reserved.